Determination of glomerular filtration rate “en passant” after high doses of iohexol for computed tomography in intensive care medicine—a proof of concept - Dejaco, Alexander; Dorn, Christoph; Paal, Michael; Gruber, Michael; Graf, Bernhard M.; Kees, Martin G. (Frontiers in Pharmacology, 2024)
Accurate assessment of renal function is of great clinical and scientific importance, as it is an important pharmacokinetic covariate of pivotal drugs. The iohexol clearance is nearly identical to the glomerular filtration rate, but its determination usually requires an intravenous injection and therefore bears intrinsic risks. This motivates to showcase an “en passant” approach to quantification of renal function without additional risk or blood sampling beyond routine care using real-world data. We enrolled 37 intensive care patients who received high doses of iohexol for computed tomography imaging, and quantified series of iohexol plasma concentrations by high-performance liquid chromatography (HPLC-UV). Iohexol clearance was derived by both log-linear regression and nonlinear least squares fitting and compared to glomerular filtration rate estimated by the CKD-EPI-2021 formulas. Nonlinear fitting not only turned out to be more accurate but also more robust in handling the irregularly timed data points. Concordance of iohexol clearance against estimations based on both creatinine and cystatin C showed a slightly higher bias (−3.44 mL/min/1.73 m2) compared to estimations based on creatinine alone (−0.76 mL/min/1.73 m2), but considerably narrower limits of agreement (±42.8 vs. 56 mL/min/1.73 m2) and higher Lin’s correlation (0.84 vs. 0.72). In summary, we have demonstrated the feasibility and performance of the “en passant” variant of the iohexol method in intensive care medicine and described a working protocol for its application in clinical practice and pharmacologic studies.